Modelagem de fatores capazes de influenciar a intenção empreendedora de estudantes de Turismo - Araújo, Fernanda Santos Gentil (2021)
The objective of this study was to analyze the interrelationships between factors capable of influencing the entrepreneurial intention of tourism students. Therefore, a structural model was proposed that integrates the Theory of Planned Behavior (T PB ) and the Institutional Environment, Entrepreneurial Learning, Family Experience and Macroenvironment constructs. The research is characterized as exploratorydescriptive with a mixed, quantitative and qualitative approach. The study p opulation were students of higher education courses in Tourism from public institutions, including Universities and Federal Institutes of Education. The sample consisted of 470 students from the bachelor's degree in tourism and technology courses in touris m management. EFA Data collection was carried out through online questionnaires, and exploratory factor analysis ( ) and structural equation modeling were performed for analysis of the collected data, in two steps: analysis of the measurement model (confirma tory factor analysis CFA ) and analysis of the structural model. In addition to the application of the questionnaires, a documental research was carried out with the pedagogical projects of the courses that participated in the research, and for the analys is of the data, the technique of content analysis, categorization and lexical analysis was used. As a result of the analysis of the PPC's, it was identified that most courses offer the discipline of entrepreneurship as mandatory or optional, and the most c ited words in their menus were "business plan", "opportunities", "tourism", "entrepreneurial characteristics", “concepts” and “entrepreneurial process”. From the confirmation of the coordinations, it was possible to identify that 20 of the 50 analyzed cour ses have a junior company, an aspect considered as an incentive for the entrepreneurial education of tourism students. It can be said that the pedagogy of the business plan, identified as predominant in the menus of the entrepreneurship disciplines, is lim ited to the construction of a business model (managerial aspects), does not focus on the personal and interpersonal dimensions of students, on creativity and innovation. It is suggested the use of case studies, games, business simulators, moments of experi ential experience. The results obtained with the questionnaires showed a strong correlation between attitude and entrepreneurial learning, and a moderate correlation between perceived behavioral control and entrepreneurial learning. Strong correlations wer e found between attitude and entrepreneurial learning and the interviewees' entrepreneurial intention. The results of this study indicate the need for greater attention in the choice of strategies to encourage entrepreneurship, as entrepreneurial training not only benefits the training of tourism students to open a business, but also encourages students to develop their skills through collaborative learning, emphasizing innovation, creativity and networking.